Business Risk Management Planning for Staff in the Division of Public Relations in a Government Agency - Putra, Herman Eka; Yuwono, Wisnu (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
In today's fast-paced and interconnected world, managing risk has become essential to effective public relations (PR) in government agencies. The public sector is highly vulnerable to a variety of risks, including reputational, legal, financial, and operational risks, which can have significant consequences for the government's ability to serve the public. This research was conducted to determine business risk management plans that might occur in the Public Relations division of a government agency and can take action to prevent and minimize the risks that will occur. This study uses a contextual descriptive analysis approach. Data collection techniques in this study are interviews with staff who have a good understanding of that field. The results of the study show that there are 4 low risks and 1 medium risk, for this reason, the public relations sector must convey to the public the positive performance of the government so that public trust increases.